A Material Model Approach on the Deflection and Crack Pattern in Different Panels of the RCC Flat Plate using Finite Element Analysis - Priya, M. P.; Priya, M. P.; Santhi, A. S. (Salehan Institute of Higher Education, 2022)
Three reinforced cement concrete (RCC) flat plate panels, namely interior, edge, and corner panels, were considered for evaluating the deflection and crack development from the column. In this study, a numerical analysis was conducted for a steel fibre-reinforced flat plate with steel fibre volumes of 0.3% and 0.4%. The study was conducted on real- and scaled-sized flat plates. We used the ABAQUS software to model and evaluate the deflection and crack patterns. An experimental study was conducted on the scaled-sized specimens to validate the finite element analysis (FEA) results. This study presents the punching shear behaviour of various panels of a flat plate with and without steel fibres. The deflection values obtained from the FEA and experiment were compared, and we found that the interior panel exhibited better results when compared to edge and corner panels. A minimum of three sided support is preferred for the stability of a larger-sized flat plate. The interior panels provided better strength and load-bearing capacity when compared to edge and corner panels. Crack patterns for different panels of a flat plate with different steel fibre volumes were analysed by comparing the FEA and experimental results. The development of cracks moved away from the column face on addition of steel fibres and changed its brittle nature. The results indicate that the crack developed from the column face is away from the critical distance d/2 from the slab-column junction (specimens with fibre), further demonstrating the stability of the structure.Â Doi: 10.28991/CEJ-2022-08-03-05 Full Text: PDF